2016
DOI: 10.4236/jssm.2016.92019
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study and the Lessons Learned from In-House Alcohol Based Hand Sanitizer Production in a District Hospital in Rwanda

Abstract: Health-care-associated infections (HCAIs) are a major global safety concern for patients, healthcare professionals and public health particularly in developing countries where access to hand washing facilities is limited due to infrastructure. Alcohol-based hand sanitizer offers a viable alternative where water sources are unreliable or insufficient. However, in resource-limited settings, the introduction of alcohol-based hand sanitizer has been slow due to economic, manufacturing and procurement challenges co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
(18 reference statements)
2
16
0
Order By: Relevance
“…2,3 When access to handwashing facilities is limited or water sources are insufficient, alcohol-based handrubs (ABHRs) offer a convenient, effective, and relatively low-cost alternative worldwide, especially for developing countries. [4][5][6] Use of hand sanitizers as preventive measures is advocated by governments and health officials in the globe to combat the disease. 7 Center for Disease Control and Prevention (CDC) recommends the use of alcohol-based hand sanitizer products that contain at least 60% ethyl alcohol (ethanol) or 70% isopropyl alcohol (isopropanol) in community settings.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 When access to handwashing facilities is limited or water sources are insufficient, alcohol-based handrubs (ABHRs) offer a convenient, effective, and relatively low-cost alternative worldwide, especially for developing countries. [4][5][6] Use of hand sanitizers as preventive measures is advocated by governments and health officials in the globe to combat the disease. 7 Center for Disease Control and Prevention (CDC) recommends the use of alcohol-based hand sanitizer products that contain at least 60% ethyl alcohol (ethanol) or 70% isopropyl alcohol (isopropanol) in community settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high demand may not serve as a marker of hand hygiene compliance using ABHR. Various studies have demonstrated high HHC using ABHR compared to soap and water when hand are not feasibly soiled (10).…”
Section: Discussion: Impact and Lessons Learntmentioning
confidence: 99%
“…This study demonstrated a component in the WHO-multi modal of hand hygiene strategy in a resource limited setting especially in Low middle income countries of Local production of ABHS 7WHO Formulation 1 was majorly considered in this project due to availability of Ethanol unlike Isopropyl alcohol which is not readily available on market nevertheless Ethanol is also cost friendly There was high demand of Locally produced alcohol hand sanitizer and this served as marker of hand hygiene compliance using sanitizers, many studies have demonstrated high hand hygiene compliance using ABHS compared to soap and water when hand are not feasibly soiled (8) Another study demonstrated poor tolerability of the WHO-recommended formulation of hand sanitizer and identified as a barrier of hand hygiene(9) however in this study we demonstrate high demand of locally produced ABHS to combat the pandemic which is a key sign to compliance and acceptability.…”
Section: Discussion: Impact and Lessons Learntmentioning
confidence: 99%